Systematic Policy and Forward Guidance at the Fed. Issue 2 (June 2014) - Plosser, Charles I.
<x xml:space="preserve">Abstract</x> The President of the Federal Reserve Bank of Philadelphia argues that the Federal Open Market Committee, by operating with a set of rules or guidelines and clearly stated objectives, could eliminate much of the second guessing about what it is doing and why, and the associated volatility in markets. The author's preference is that the FOMC formulate its policy as a "reaction function" that can be easily explained to the public. As an example of such a reaction function, he cites the proposal of Stanford economist John Taylor, whose "Taylor Rule" calls for setting the nominal fed funds rate based on three factors: (1) the economy's long‐run real interest rate; (2) the deviation of inflation from the central bank's target or goal; and (3) an adjustment of the funds rate to departures of real GDP from some measure of "potential" GDP. Although many variations on Taylor's original recommendations could work, the author believes the FOMC should seek to develop a consensus on how it will react to future economic events. Even a qualitative description of such a reaction function would be a step forward. Taking such a systematic approach will improve the effectiveness of monetary policy in both normal times and more unusual or extreme circumstances, such as when policy is constrained by the lower zero bound on interest rates. The author also suggests that a recent (March 19) FOMC statement took a step in this direction when it moved to a qualitative form of forward guidance by stating that the Committee will be assessing progress—both realized and expected—toward its policy objectives.